2018
DOI: 10.1016/j.cels.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Modulation of Transcriptional Bursting Enables Sensitive and Rapid Gene Regulation

Abstract: Gene regulation is a complex non-equilibrium process. Here, we show that quantitating the temporal regulation of key gene states (transcriptionally inactive, active, and refractory) provides a parsimonious framework for analyzing gene regulation. Our theory makes two non-intuitive predictions. First, for transcription factors (TFs) that regulate transcription burst frequency, as opposed to amplitude or duration, weak TF binding is sufficient to elicit strong transcriptional responses. Second, refractoriness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 61 publications
12
91
0
Order By: Relevance
“…Also, the number of CCNA2 copies actively expressing in a cell do not reflect on the overall mRNA count in that cell-there can be cells with very high mRNA count but fewer than two copies actively expressing and vice versa. This demonstrates the stochastic nature of transcriptional bursts and gene regulation via the modulation of burst frequency [38]. This might also suggest a possible decoupling between the activities of different alleles within a nucleus where each is agnostic of others' transcriptional status unlike as reported recently for the bacterial system [39].…”
Section: Discussionsupporting
confidence: 63%
“…Also, the number of CCNA2 copies actively expressing in a cell do not reflect on the overall mRNA count in that cell-there can be cells with very high mRNA count but fewer than two copies actively expressing and vice versa. This demonstrates the stochastic nature of transcriptional bursts and gene regulation via the modulation of burst frequency [38]. This might also suggest a possible decoupling between the activities of different alleles within a nucleus where each is agnostic of others' transcriptional status unlike as reported recently for the bacterial system [39].…”
Section: Discussionsupporting
confidence: 63%
“…TGF‐β1 stimulation, in contrast, led to a sustained increase in burst sizes. Frequency modulation has been demonstrated for c‐fos dependent transcription after serum or zinc induction (Senecal et al , ), light‐controlled transcription by the White Collar Complex in Neurospora (Li et al , ), and dose‐dependent transcriptional regulation by ligand‐bound steroid receptors (Larson et al , ). Using targeted perturbations, it has further been shown that frequency modulation and polymerase pause release are key regulatory aspects of transcriptional regulation, while RNAP2 recruitment occurs subsequent to burst initiation (Bartman et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Frequency modulation of target gene expression has previously been demonstrated for other cellular processes such as c-fos dependent transcription after serum or zinc induction (Senecal et al, 2014), light-controlled transcription by the White Collar Complex (WCC) in Neurospora (Li et al, 2018) and dose-dependent transcriptional regulation by ligand-bound steroid receptors . Using targeted perturbations it has further been shown that frequency modulation and polymerase pause release are key-regulatory aspects of transcriptional regulation, while RNAP2 recruitment occurs subsequent to burst initiation (Bartman et al, 2019).…”
Section: The K370/382 Methylation-acetylation Switch Contributes To Tmentioning
confidence: 99%